The molecular origin of high performance in ternary organic photovoltaics identified using a combination of in situ structural probes. Issue 3 (20th December 2022) - Luke, Joel; Jo, Yong-Ryun; Lin, Chieh-Ting; Hong, Soonil; Balamurugan, Chandran; Kim, Jehan; Park, Byoungwook; Lee, Kwanghee; Durrant, James R.; Kwon, Sooncheol; Kim, Bong-Joong; Kim, Ji-Seon
Abstract : Using a combination of in situ techniques we unravel the role of the tertiary component in the morphological evolution of a model organic photovoltaic ternary blend system and show how this results in a higher efficiency and more stable device. Abstract : A ternary blend, wherein a tertiary acceptor is incorporated into a donor:non-fullerene acceptor (NFA) binary blend has emerged as a promising strategy for improving power conversion efficiency and stability of organic bulk heterojunction photovoltaics (OPVs). However, the effects of the tertiary component remain elusive due to the complex variation of crystallinity and morphology of donor and acceptor phases during thermal annealing. Herein a combination of in situ transmission electron microscopy and X-ray diffraction spectroscopy utilized during annealing identifies that (1) the addition of the tertiary component (O-IDFBR) delays the glass transition temperature of edge-on-oriented polymer donor (P3HT), prohibits the glass transition of face-on-oriented polymer donor (P3HT), broadens the crystallization temperature of O-IDTBR, and enhances the overall crystallinity of the donor and acceptor phases (P3HT and O-IDTBR), and (2) the ternary component induces homogeneously distributed nanoscale domains rather than a microscale separation between the donor and acceptor as observed in the binary blend. The optimized nanoscale domain morphology, driven by slower crystallization and enhanced overall crystallinity leads to a more stable morphology, resulting in superior device performance and stability.